What insights do patients and caregivers have on acute kidney injury and posthospitalisation care? A single-centre qualitative study from Toronto, Canada. Issue 6 (15th June 2018) - Silver, Samuel A; Saragosa, Marianne; Adhikari, Neill K; Bell, Chaim M; Harel, Ziv; Harvey, Andrea; Kitchlu, Abhijat; Neyra, Javier A; Wald, Ron; Jeffs, Lianne
Abstract : Objectives: Hospitalisation with acute kidney injury (AKI) is associated with short-term and long-term adverse events, but patient and caregiver experiences with AKI are not well described. We sought to better understand patient and caregiver perspectives after a hospitalisation with AKI to inform discharge strategies that may improve outcomes for this high-risk population. Design: Qualitative study with semistructured interviews. Setting: Tertiary care hospital in Toronto, Ontario, Canada. Participants: Adult patients (n=15) who survived a hospitalisation with Kidney Disease Improving Global Outcomes stage 2 or 3 AKI from May to December 2016. We also interviewed five patient caregivers. We required patients to have no previous evidence of severe chronic kidney disease (ie, prior receipt of dialysis, previous kidney transplantation or pre-existing estimated glomerular filtration rate (eGFR) under 30 mL/min/1.73 m 2 ). Results: We identified three over-arching themes: (1) prioritisation of conditions other than AKI, reflected by the importance placed on other comorbidities and the omission of AKI as part of the ongoing medical history; (2) variability in comprehension of the significance of AKI, represented by minimal knowledge of the causes and symptoms associated with AKI, along with misinformation on the kidneys' ability to self-repair; and (3) anxiety from discharge planning and competing health demands, illustrated by complicated discharge plans involving multiple specialist appointments. Conclusions: Patients and caregivers view AKI as a short-term and reversible condition, giving it little thought during the postdischarge period. As a result, reliance on patients and caregivers to report an episode of AKI to their outpatient physicians is unlikely to be successful. Patient-centred tools and decision aids are needed to bridge the gap between a hospitalisation with AKI and the safe transition to the outpatient setting.